2016
DOI: 10.3139/120.110869
|View full text |Cite
|
Sign up to set email alerts
|

Multi-response milling process optimization using the Taguchi method coupled to grey relational analysis

Abstract: An efficient method based on Taguchi's design of experiment coupled with the grey relational analysis was studied, concentrating on the optimization of process parameters over surface roughness, cutting force and tool wear rate in milling of mild steel. This study consists of three stages: experimental work, single response optimization using Taguchi's S/N value and multi-response optimization using grey relational analysis. In the first stage, the experimental work was carried out using Taguchi's design of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The better surface roughness was obtained with minimum value of federate. 50,51
Figure 7.(a) Three-dimensional surface plots for interaction effects of cutting speed and feed rate, (b) cutting speed and depth of cut and (c) feed rate and depth of cut on surface roughness.
…”
Section: Resultsmentioning
confidence: 99%
“…The better surface roughness was obtained with minimum value of federate. 50,51
Figure 7.(a) Three-dimensional surface plots for interaction effects of cutting speed and feed rate, (b) cutting speed and depth of cut and (c) feed rate and depth of cut on surface roughness.
…”
Section: Resultsmentioning
confidence: 99%
“…In order to verify the dynamic test, designed dynamometer was undergone the actual machining test in L-Mill 55 vertical machining centre. The experiments were planned and carried out with mild steel based on Taguchi's L9 orthogonal array [44]. The experimental setup for measuring the cutting force was presented in Figure 10.…”
Section: Machining Testmentioning
confidence: 99%
“…Rao and Murthy 15 used Response Surface Methodology (RSM), Artificial Neural network (ANN) and Support Vector Machines (SVM) to investigate the machinability characteristics of AISI 316 steel and concluded that cutting speed is the most influencing factor for machine vibration. Shankar et al 16 opined that best surface finished might be obtained in case minimum feed rate. Shankar et al 17 expressed that an increase in depth of cut increase the flank wear and cutting force simultaneously.…”
Section: Related Workmentioning
confidence: 99%